2021
DOI: 10.14574/ojrnhc.v21i2.674
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Student Perceptions of Planning and Implementing a Student-led, Faculty-guided Rural Health Clinic

Abstract: Purpose:To develop an interprofessional student-led, faculty-guided clinic in a rural, medically underserved area in Wisconsin through applying an existing innovative clinical education model.A local university provides a system for training and practice of interprofessional students in a rural community increasing access to preventive health care to individuals and families in rural medically underserved communities. The primary aim of the project was to qualitatively describe perceptions of interprofessional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“… Bostick (2014) 69 Focus groups Campbell et al (2013) 23 SS one-on-one interviews Chen et al (2014) 26 SS one-on-one interviews Frakes et al (2014) 39 Structured interview X ? Frie et al (2021) 62 Open-ended questions Guirguis et al (2011) 80 SS one-on-one interviews Hamilton (2020) 41 SS one-on-one interviews …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Bostick (2014) 69 Focus groups Campbell et al (2013) 23 SS one-on-one interviews Chen et al (2014) 26 SS one-on-one interviews Frakes et al (2014) 39 Structured interview X ? Frie et al (2021) 62 Open-ended questions Guirguis et al (2011) 80 SS one-on-one interviews Hamilton (2020) 41 SS one-on-one interviews …”
Section: Resultsmentioning
confidence: 99%
“…The third most frequently reported learning outcome associated with SRC participation revolved around empathy/compassion for underserved individuals (n = 34), 15 , 18 , 25 , 27–29 , 42 , 53 , 55 , 57 , 59 , 62 , 75 , 83–87 in particular improving attitudes towards, 15 , 18 , 25 , 28 , 34 , 88 as well as awareness and understanding and of the needs and social reality of, the underserved. 19 , 22 , 29 , 31 , 35 , 36 , 55 , 57 , 59 , 60 , 62 , 66 , 68 , 70 , 75 , 76 , 82 , 84 , 86 , 89–92 Though one study reported no change in overall attitudes towards homeless patients. 93 Finally, improved skills working with indigenous populations were noted as a learning outcome in one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of this experience for learning was opportune, despite the challenges it created. Frie et al 14 report the importance of team communication within interprofessional teams in enhancing collaboration of health profession students. Internship students in this experience quickly learned how to collaborate and work as a team in virtual ways.…”
Section: Discussionmentioning
confidence: 99%
“…Student-led teams find the importance of their own leadership opportunities while assessing their community needs. 14 Throughout the time of this work, community partners continued to reach out, asking for help to provide their patrons with basic human needs; the most important to them, connection. This ongoing demand required the student teams to effectively work together to deliver innovative service.…”
Section: Discussionmentioning
confidence: 99%